External Stimuli Responsive 2D Charge Transfer Polymers. Issue 2 (2nd December 2016) - Zhang, Zhuolei; Xu, Beibei; Xu, Bolei; Jin, Lei; Dai, Hai‐Lung; Rao, Yi; Ren, Shenqiang
Abstract : 2D conjugated charge‐transfer polymers hold the fundamental importance of both atomically defined molecular structures and unique spatial confinement for distinctive and exotic material properties. However, such 2D crystalline networks exhibit a fundamental processing challenge in polymer science and molecular assembly, which precludes emerging applications for 2D polymers. Here, an operationally simple solvothermal crystallization of conjugated charge‐transfer polymer into a freestanding and ultrathin 2D nanosheet directed by electrostatic recognition, π–π interaction, and charge‐transfer complexation is reported. High flexibility and 3D stacking capability of ultrathin 2D conjugated polymers provide a robust solution‐processing platform to uncover their emerging optoelectronics and multisensing capabilities. Resembling covalent organic framework assembly, these materials potentially open up a new exciting field of 2D conjugated networks with the structure flexibility and materials‐by‐design opportunities for all organic electronics. Abstract : A freestanding and ultrathin 2D conjugated charge‐transfer polymeric nanosheet is crystallized and directed by electrostatic recognition, π–π interaction, and charge‐transfer complexation, which provide a robust solution‐processing platform to uncover their emerging multifunctionalities for all organic optoelectronics and multisensing capabilities.